2023
DOI: 10.1063/5.0141815
|View full text |Cite
|
Sign up to set email alerts
|

Porous media flooding mechanism of nanoparticle-enhanced emulsification system

Abstract: This study carried out interfacial tension (IFT) test, sand surface element analysis and scanning electron microscope (SEM) image, rock-oil-emulsification system interaction test, microstructure, droplet size distribution and stability of oil in water (O/W) emulsion to clarify the porous media flooding mechanism of hydrophilic Nano-SiO2 enhanced emulsification system. Results shows that by adding small amount of Nano-SiO2 (0.01 wt.%) into anionic surfactant fatty alcohol polyoxyethylene ether sodium hydroxypro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…9 On the other hand, oil-in-water emulsions are generated during surfactant flooding of rocks carrying heavy oils 10−13 and flooding of anionic surfactant solutions containing silica nanoparticles. 14 The existing literature contains various studies aimed at characterizing the rag layers and determining the causes for their stability. Varadaraj and Brons 15 observed that the rag layer is a complex fluid composed of flocs of water droplets in oil, water droplets stabilized by submicron-sized sediments, double emulsions of oil−water−oil type, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 On the other hand, oil-in-water emulsions are generated during surfactant flooding of rocks carrying heavy oils 10−13 and flooding of anionic surfactant solutions containing silica nanoparticles. 14 The existing literature contains various studies aimed at characterizing the rag layers and determining the causes for their stability. Varadaraj and Brons 15 observed that the rag layer is a complex fluid composed of flocs of water droplets in oil, water droplets stabilized by submicron-sized sediments, double emulsions of oil−water−oil type, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For example, water-in-oil emulsions are generated during water/steam flooding of porous rocks for heavy oil recovery. , They are also formed when bitumen is extracted from bitumen-carrying sand using water . On the other hand, oil-in-water emulsions are generated during surfactant flooding of rocks carrying heavy oils and flooding of anionic surfactant solutions containing silica nanoparticles …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation